0
$\begingroup$

I'm considering a typical profit-maximization problem:

\begin{equation} \label{optimization1} \begin{aligned} & \underset{K,L}{\text{max}} & & P Y - r K - w L \\ \end{aligned} \end{equation}

where $r$ is the interest rate and $w$ is the wage rate.

The production function can be Cobb-Douglas,

$Y=AK^{\alpha}L^{\beta}$

where $0\leq \alpha \leq 1$ and $0\leq \beta \leq 1$. Or it can be a CES production function.

I would like to find the solution for $K$ and $L$ in either case of production function.

My code in the case of Cobb-Douglas, for example, is:

Y = A k^a L^b;
PROF = P Y - r k - w L;
z1 = D[PROF, k];
z2 = D[PROF, L];
Simplify[Solve[{z1 == 0, z2 == 0}, {k, L}], {0 <= a <= 1 && 0 <= b <= 1 && 
A > 0 && k > 0 && L > 0 && P > 0 && r > 0 && w > 0 && PROF > 0}]

And I get a very weird solution as follows. enter image description here

Can anyone help in finding what went wrong? Thanks!

$\endgroup$
  • $\begingroup$ Why are you so convinced that anything went wrong? However, you have inequality constraints on k and L, so ypu need to solve the full set of KKT conditions. And those can usually only be solved when numerical values for all parameters are given. $\endgroup$ – Henrik Schumacher Aug 10 at 4:05
  • $\begingroup$ @Henrik: You can sense that the solution is weird once you solve it manually and compare. (In fact, it is easy to find on the internet a note that describes the process of solving this kind of maximization problem.) $\endgroup$ – ppp Aug 12 at 9:25
  • $\begingroup$ The point is this: You have to make this problem intersting to other users, not me. It is unlikely that users perform long computations before they decide to help you or not. $\endgroup$ – Henrik Schumacher Aug 12 at 13:11
2
$\begingroup$

Try

Y = A k^a L^b;
PROF = P Y - r k - w L;
z1 = D[PROF, k];
z2 = D[PROF, L];
sol=Together[Simplify[Solve[{z1 == 0, z2 == 0}, {k, L}], {0 <= a <= 1 && 0 <= b <= 1 && a + b + c == 1 && A > 0 && k > 0 && L > 0 && P > 0 && r > 0 &&  w > 0 && PROF > 0}][[1]]]
{k, L} /. sol // FullSimplify
$\endgroup$
  • 2
    $\begingroup$ It's a bit nicer, imo, if we introduce another parameter c and add the assumption a + b + c == 1 to Simplify. (+1) $\endgroup$ – Michael E2 Aug 12 at 15:28
  • $\begingroup$ @MichaelE2 Edited according to your hint. Thanks. $\endgroup$ – Cesareo Aug 12 at 15:57

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.